The habit of consuming herbal reviewed from the level of knowledge and culture in pregnant women in Tunge Village, Wates Sub-District - Wulandari, Anggrawati; Sulistyowati, Ririn; Siwi, Retno Palupi Yonni (Institute of Computer Science (IOCS), 2024)
Among pregnant women are often also found mothers who consume herbs, with various purposes such as to eliminate nausea, vomiting, disappear lethargy and weakness, strengthen the fetus and calm the mind. The purpose of this research is to analyze the relationship between consumting herbal habits in terms of the level of knowledge and culture among pregnant women. The research design used descriptive Analytic with a cross sectional approach. The sampling technique uses a total sampling of 38 respondents. Data were analyzed using Spearmans correlation. The results of the study were obtained mostly namely 18 (48%) respondents with a good level of knowledge, and did not consume herbal medicine during pregnancy. In cultural factors, the vast majority, namely 13 (34.5%) respondents with moderate culture, do not consume herbal medicine. From the results of the Spearman's Rho test, a probability value of 0.007 is obtained. From the results of the study, it can be analyzed that level knowledge and culture have a close relationship with the habits of mothers consuming herbal medicine during pregnancy. Good level knowledge will affect the formation of good behavior. In contrast to culture, a weak culture makes mothers not consumting herbal.